Exploiting Polyphenol-Mediated Redox Reorientation in Cancer Therapy - Lei Li; Ping Jin; Yueyue Guan; Maochao Luo; Yu Wang; Bo He; Bowen Li; Kai He; Jiangjun Cao; Canhua Huang; Jingquan Li; Zhisen Shen (MDPI AG, 2022)
Polyphenol, one of the major components that exert the therapeutic effect of Chinese herbal medicine (CHM), comprises several categories, including flavonoids, phenolic acids, lignans and stilbenes, and has long been studied in oncology due to its significant efficacy against cancers in vitro and in vivo. Recent evidence has linked this antitumor activity to the role of polyphenols in the modulation of redox homeostasis (e.g., pro/antioxidative effect) in cancer cells. Dysregulation of redox homeostasis could lead to the overproduction of reactive oxygen species (ROS), resulting in oxidative stress, which is essential for many aspects of tumors, such as tumorigenesis, progression, and drug resistance. Thus, investigating the ROS-mediated anticancer properties of polyphenols is beneficial for the discovery and development of novel pharmacologic agents. In this review, we summarized these extensively studied polyphenols and discussed the regulatory mechanisms related to the modulation of redox homeostasis that are involved in their antitumor property. In addition, we discussed novel technologies and strategies that could promote the development of CHM-derived polyphenols to improve their versatile anticancer properties, including the development of novel delivery systems, chemical modification, and combination with other agents.